2017
DOI: 10.3390/ma11010033
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study on Intermetallic Pd–Cu Alloy with Cover Layer Pd as Efficient Catalyst for Oxygen Reduction Reaction

Abstract: Detailed density functional theory (DFT) calculations of the adsorption energies (Ead) for oxygen on monolayer Pd on top of the Pd–Cu face-centered cubic (FCC) alloy and intermetallic B2 structure revealed a linear correspondence between the adsorption energies and the d-band center position. The calculated barrier (Ebarrier) for oxygen dissociation depends linearly on the reaction energy difference (ΔE). The O2 has a stronger adsorption strength and smaller barrier on the intermetallic Pd–Cu surface than on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…However, in the as synthesised IMC PdIn, with In being an element with lower electronegativity than Pd, the electronic structure of Pd is changed, thereby reducing the DOS near the Fermi energy level for Pd in PdIn. The decrease in DOS with the formation of the intermetallic compounds was also observed in a previous report . Hence a direct consequence of the decrease in DOS near fermi level in PdIn leads higher adsorption energy of styrene, leading to its preferential desorption over further hydrogenation to ethylbenzene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the as synthesised IMC PdIn, with In being an element with lower electronegativity than Pd, the electronic structure of Pd is changed, thereby reducing the DOS near the Fermi energy level for Pd in PdIn. The decrease in DOS with the formation of the intermetallic compounds was also observed in a previous report . Hence a direct consequence of the decrease in DOS near fermi level in PdIn leads higher adsorption energy of styrene, leading to its preferential desorption over further hydrogenation to ethylbenzene.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in DOS with the formation of the intermetallic compounds was also observed in ap reviousr eport. [25] Hence ad irect consequenceo ft he decrease in DOS near fermi level in PdIn leads higher adsorption energy of styrene, leadingt oi ts preferential desorption over further hydrogenation to ethylbenzene.…”
Section: Phenylacetylener Eductionmentioning
confidence: 99%
“…The inset of Figure e shows a supercell structure where Au atoms are inserted alternately between adjacent Pd atoms. Introducing the Au atoms into the Pd (111) planes altered the structural and electronic properties of the PdAu system due to lattice mismatch and induced charge transfer (Figure S7, Supporting Information) …”
Section: Resultsmentioning
confidence: 99%
“…The atomic coordinates were relaxed to ensure an energy of 10 −5 eV and a force tolerance of 0.01 eV −1 . The adsorption energy, E ads was defined by the following formulaEads=EnormalPdAu111+H2EnormalPdAufalse(111false)NnormalHEH2normal/2/NnormalHwhere E PdAu(111)+H2 is the total energy of the PdAu(111) slab with adsorbed H 2 , E PdAu(111) is the total energy of the PdAu(111) slab, E H2 is the total energy of an H 2 molecule, and N H denotes the total number of hydrogen atoms.…”
Section: Methodsmentioning
confidence: 99%
“…synthesized face‐centered tetragonal (fct)‐FePd/Pd nanoparticles and demonstrated that fct‐FePd/Pd has higher ORR activity and durability than fcc‐FePd in acidic media. Results from a recent theoretical study on the catalyzing reduction of oxygen of ordered PdCu demonstrated that the addition of Cu can regulate charge transfer from Cu to Pd to reduce the Pd−O binding energy with a change in the d‐band center. To further optimize the oxygen binding strength, the addition of a third element to form an ordered Pd‐based ternary nanoparticle is a viable method …”
Section: Introductionmentioning
confidence: 99%